Genotype-phenotype correlation on 45 individuals with West syndrome - Krey, Ilona; Krois-Neudenberger, Janna; Hentschel, Julia; Syrbe, Steffen; Polster, Tilman; Hanker, Britta; Fiedler, Barbara; Kurlemann, Gerhardt; Lemke, Johannes R. (European journal of paediatric neurology, 2020)
West syndrome is an epilepsy syndrome characterized by repetitive epileptic spasms (ES) and hypsarrhythmia, typically leading to developmental delay/intellectual disability (DD/ID). It is considered a classic epileptic encephalopathy (EE). We designed a diagnostic sequencing panel targeting 131 genes associated with epilepsy and/or EE and screened a cohort of 45 individuals with clinical diagnosis of West syndrome. We identified disease-causing single nucleotide variants in 11 out of 45 individuals affecting genes commonly associated with West syndrome (such as CDKL5, ARX) but also in genes predominantly linked to other epileptic disorders (such as DEPDC5, SCNIA, WDR45, AARS). Panel analysis revealed copy number variants in two additional cases, comprising a 6,7 Mb Duplication on chromosome 2 including SCN2A and SCN3A and a supernumerary marker chromosome 15 leading to an overall diagnostic yield of 29% (13/45). In our cohort, individuals with a disease-causing variant had significantly more severe phenotypes with respect to DD/ID, therapy resistant epilepsy and cerebral atrophy compared to genetically unclarifled cases. In addition to investigating the genotypic spectrum of West syndrome, we compared the phenotypic spectrum of clarified versus unclarifled cases. Our study illustrates that West syndrome is an electroclinical syndrome caused by various genetic disorders. Individuals without detectable genetic cause might have less encephalopathy leading to a less severe course. (C) 2019 European Paediatric Neurology Society. Published by Elsevier Ltd. All rights reserved.
Available online: 26 November 2019
Gesehen am 02.07.2020